The Integration of Education for Sustainable Development (ESD) for Sustainable Development of Doctoral Study Program in Islamic Education Management - Hidayati, Suci; Daroini, Slamet; Astuti, Rini Nafsiati; Ajmain, Muhammad Talhah; Zuhriyah, Indah Aminatuz (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This study aims to examine in depth the integration of Education for Sustainable Development (ESD) in the Sustainability Development of the Doctoral Study Program in Islamic Education Management at UIN Maulana Malik Ibrahim Malang. Education For Education for Sustainable Development (ESD) is an educational process that aims to provide students and lecturers with the knowledge, skills, attitudes, and values ”‹”‹needed to create a more sustainable future. This study uses a qualitative approach with an explanatory case study type. Data collection techniques are carried out through in-depth interviews, observations, surveys, and documentation tests. Data analysis through the stages of condensation and data display and conclusions. The results of this study of; 1) ESD-based curriculum design for sustainable development Doctoral Study Program of Islamic Education Management at UIN Maliki Malang; 2) Implementation of ESD integration based on Islam in learning the development of sustainable study programs and the process of implementing ESD integration based on Islam in learning the development of sustainable study programs of Doctoral Study Program of Islamic Education Management at UIN Maliki Malang; and 3) Overview of the ESD integration framework for the development of sustainable study programs of doctoral study programs of Islamic Education Management.